FACTOR AFFECTING THE EFFECTIVENESS OF THE LOGISTICS MANAGEMENT SUCCESS OF COMMUNITY ENTERPRISE ENTREPRENEURS IN THE UPPER NORTHEASTERN PROVINCE - Promthong, Sasiprapa (Journal of Social Science and Cultural, 2023)
The objectives of this research article were to 1) To study the causal factors affecting the effectiveness of logistics management of community enterprise entrepreneurs in the upper northeastern provinces. 2) To examine the consistency of the causal relationship model of logistics management effectiveness of community enterprise entrepreneurs in the upper northeastern provinces. This research was a quantitative research methodology. The sample group consisted of 160 entrepreneurs of the upper northeastern provinces who were randomly sampled. The instrument used to collect data was a 5-level questionnaire. Data were analyzed by descriptive statistics. and structural equation model analysis. The findings are 1) Marketing Logistics Management Potential It has a positive influence on the efficiency of logistics management of enterprises in the upper northeastern provinces. 2) Potential of transport logistics management There was a positive influence on the effectiveness of logistics management of enterprises in the upper northeastern provinces. Community enterprises are therefore resilient and powerful enough to grow into independent business owners. associated government sector parties Additionally, In order to aid in production and sales promotion, innovation and technology expertise should also be present. In order for community enterprise organizations to propel themselves to become viable small and medium enterprises, they need to find market sources to support the products they produce. For simplicity and speed, community businesses should embrace technology to assist with information management. Community businesses should employ data management technology to store data quickly and conveniently and to support company continuity. This technology also aids in transportation, which increases efficiency.